The effect of excess PbO on crystal structure, microstructure and dielectric properties of (Pb0.50Sr0.50)TiO3 ceramics - Sumang, Rattiphorn; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2013)
Lead strontium titanate [(Pb50Sr50)TiO3; PST] ceramics were fabricated by the conventional solid state reaction method using calcination and sintering temperatures of 950°C and 1250°C. To prevent PbO evaporation during the firing processes, excess PbO was added to the samples in varying amounts from 0-10 wt.%. It was found that PST powders indexed in a tetragonal structure. Impurity phases were detected in the calcined powders which had excess PbO higher than 3 wt%. A pure perovskite phase was obtained from all ceramic samples. The lattice parameters a, c and the c/a ratio decreased with an increasing excess of PbO. The average particle size and the average grain size increased with the increase of PbO. The porous microstructure slightly decreased with an increasing amount of PbO, up to 1 wt.%, then slightly increased with higher excess PbO. The density can be improved by adding 1 wt.% of excess PbO. The dielectric constant increased from 7500 for the 0 wt.% sample to 8300 for the 1 wt%. This was followed by reductions for 3, 5 and 10wt.%. The Curie temperature and transition enthalpy slightly increased with an increase amount of PbO until 1 wt.%, then slightly decreased, for the higher excess PbO. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dielectric properties; Excess PbO; lead strontium titanate; tetragonality